Sugar Nucleotide Recognition by Klebsiella pneumoniae UDP-d-Galactopyranose Mutase: Fluorinated Substrates, Kinetics and Equilibria - Errey, James C. (2009)
A series of selectively fluorinated and other substituted UDP-d-galactose derivatives have been evaluated as substrates for Klebsiella pneumoniae UDP-d-galactopyranose mutase. This enzyme, which catalyses the interconversion of the pyranose and furanose forms of galactose as its UDP adduct, is a prospective drug target for a variety of microbial infections. We show that none of the 2″-, 3″- or 6″-hydroxyl groups of UDP-d-galactopyranose are essential for substrate binding and turnover. However, steric factors appear to play an important role in limiting the range of substitutions that can be accommodated at C-2″ and C-6″ of the sugar nucleotide substrate. Attempts to invert the C-2″ stereochemistry from equatorial to axial, changing d-galacto- to d-talo-configuration, in an attempt to exploit the higher percentage of furanose at equilibrium in the talo-series, met with no turnover of substrate.